Westernisasi Ilmu dalam Islamic Worldview - Herdina Pratiwi (State Islamic Institute of Madura, 2020)
The current technological advances, making various informations easily spread throughout the world. It includes the entry of foreign culture (Westernization) into the Indonesian State. This westernization does not only have impact on politics, culture, region and technology, but in its development, westernization began to go into science. This research uses a literary study method, namely data collection activities by conducting a review of various books, literature, notes and reports realting to the topic discussed. As a result, it can be seen that knowledge Westernization occurs due to the development of shopist who generally have an impact on knowledge in the West. Knowledge in the West as a whole only relies on ratio in describing various things. So the process has strengthened the thesis of the knowledge Westernization. Knowledge in the West has the characteristic of removing the value of belief and spirituality, so this concept breeds secularization. Whereas secularization itself is not only a western worldview that is not Islamic, but also contrary to Islamic teachings. Secularization eliminates revelation as a source of knowledge and negates theÂ role of God in the scientific procces. This is what makes the knowledge Westernization increasingly clear.